Spin-momentum coupled Bose-Einstein condensates with lattice band pseudospins - M. A. Khamehchi (Nature Portfolio, 2016)
The optical trapping of ultracold atoms allows for the simulation and controlled exploration of phenomena normally found in condensed matter systems. Here, the authors demonstrate spin–orbit coupling between lattice band pseudospins in a Bose-Einstein condensate of ultracold atoms.